On Mann’s Method with Viscosity for Nonexpansive and Nonspreading Mappings in Hilbert Spaces - Nawab Hussain; Giuseppe Marino; Afrah A. N. Abdou (Abstract and Applied Analysis)
In the setting of Hilbert spaces, inspired by Iemoto and Takahashi (2009), we study a Mann’s method with viscosity to approximate strongly (common) fixed points of a nonexpansive mapping and a nonspreading mapping. A crucial tool in our results is the nonspreading-average type mapping.